Ultrafine garlic powder alleviates non-alcoholic steatohepatitis by inhibiting hepatocyte ferroptosis and modulating ERK-dependent oxidative stress - Yu, Junhui; Shao, Ningning; Yang, Jianming; Yang, Long; Hong, Kaiwen; Chen, Yuzhu; Zhao, Xiaoming; Yu, Hongzhi; Zhang, Tao; Dong, Jinrui (Frontiers in Pharmacology, 2025)
IntroductionNonalcoholic steatohepatitis (NASH) is a chronic liver disease associated with oxidative stress and ferroptosis, leading to liver injury and fibrosis. Garlic, renowned for its antioxidant and hepatoprotective properties, is commonly used in traditional medicine. Ultrafine powder technology enhances the physicochemical properties of natural products, improving their bioavailability and efficacy. This study explores the protective effects of ultrafine garlic powder (UGP) on NASH and its underlying mechanisms.MethodsIn this study, UGP was prepared by high-speed particle collision technology and compared with traditional garlic powder (TGP).ResultsUGP exhibited a particle size (d(0.5) of approximately 4 μm) that is 30 times smaller than TGP, showing significantly smaller particle size and lower contact angle (UGP=59.775°vs TGP=83.545°). UGP also demonstrated improved solubility and dispersibility, along with an enrichment of key organosulfur compounds such as allicinAllicin, Alliin, SAC, and GSAC. In vitro, UGP significantly reduced palmitic acid-induced ROS production (n=4, p< 0.0001), prevented mitochondrial dysfunction (n=4, p=0.0035), and thereby reduced hepatic stellate cell activation. UGP lowered intracellular Fe2+ levels in hepatocytes from 68.72% to 34.48% (n=4) and significantly protected hepatocytes from erastin-induced ferroptosis (cell viability: UGP treatment 23.46% vs erastin stimulation 53.91%, n = 4, p <0.0001).In the acute liver fibrosis model induced by methionine- and choline-deficient diet supplemented with 60 kcal% fat (CDHF), UGP significantly improved liver histology. Compared to the model group, the liver/body weight ratio of mice was significantly restored (n=4, p<0.0001), and histopathological staining showed a substantial improvement in liver damage. Biochemically, UGP significantly reduced the levels of liver collagen, triglycerides, and cholesterol (n = 6, p < 0.0001). Fibrosis-related mRNA and pro-inflammatory mRNA expression were significantly decreased. Western blot results showed that UGP significantly inhibited the activation of p-ERK signaling. In the chronic liver fibrosis model induced by a diet with 60 kcal% fat (HFD), UGP demonstrated similar therapeutic effects. RNA-seq analysis revealed that UGP modulated key pathways, including fatty acid metabolism and the MAPK signaling pathway, and suppressed ROS production, further highlighting its therapeutic potential in NASH treatment.DiscussionTaken together, these data suggest that UGP alleviates NASH by inhibiting hepatocyte ferroptosis and modulating ERK-dependent oxidative stress, supporting its potential as a therapeutic agent.